Identifikasi Risiko dalam Beberapa Kategori di Pendidikan Vokasi - Rina Sandora; Hwihanus (Vokasi : Jurnal Riset Akuntansi, 2026)
Abstract Economic changes, educational policies, and the changing needs of educators along with technological advances and global demands make educational institutions face challenges in creating flexible and responsive educational strategies to improve the quality of education. This study aims to provide an in-depth understanding of the risks for vocational education in achieving its vision and mission. These challenges can be addressed by implementing risk management in several risk categories. The organization identifies the impact criteria and likelihood of risks on a scale of 1-5, conducts risk input, obtains risk matrices and priorities, creates a risk appetite report, conducts risk management actions, and reports on risk monitoring. The results of the initial risk level with residual risk indicate a decrease in the risk level. The conclusion is that the implementation of risk management can control existing risks due to the mitigation carried out. There are three high risks after risk management becomes moderate risk, low risk and enters the risk appetite and risk tolerance categories.